Advances in chimeric antigen receptor T cells. Issue 6 (November 2020) - Beyar-Katz, Ofrat; Gill, Saar
Abstract : Purpose of review: To discuss the important advances in CAR T cell therapy over the past year, focusing on clinical results where available. Recent findings: Approximately 30 years after they were first conceived of and 15 years after the first small-scale single-center clinical trials, the past 3 years represent a major milestone in the development of CAR T cells. In the United States, the Food and Drug Administration (FDA) approved Tisagenlecleucel for the treatment of relapsed/refractory B-ALL and Axicabtagene Ciloleucel, for adults with relapsed/refractory diffuse large B cell lymphoma (R/R DLBCL) in 2017. Tisagenlecleucel received a second indication in adults with R/R DLBCL in 2018. Regulatory approval for CAR T cells was then granted in Europe, Canada, Australia, and Japan. Most recently, in July 2020 the FDA granted regulatory approval to a third CAR T cell product, Brexucabtagene Autoleucel for mantle cell lymphoma. All products target the CD19 antigen but differ in the costimulatory molecule within the CAR construct. Currently, it is unknown whether there are any differences in clinical activity or toxicity between these products. Summary: The CAR T cell the platform is evolving at a rapid pace and is expected to further improve the therapeutic outcomes of hematological malignancies.